Reducing Willow Wood Fuel Emission by Low Temperature Microwave Assisted Hydrothermal Carbonization - Diaz-Robles, L (JOURNAL OF VISUALIZED EXPERIMENTS, 2019)
Biomass is a sustainable fuel, as its CO2 emissions are reintegrated in biomass growth. However, the inorganic precursors in the biomass cause a negative environmental impact and slag formation. The selected short rotation coppice (SRC) willow wood has a high ash content ((x) over bar = 1.96%) and, therefore, a high content of emission and slag precursors. Therefore, the reduction of minerals from SRC willow wood by low temperature microwave assisted hydrothermal carbonization (MAHC) at 150 degrees C, 170 degrees C, and 185 degrees C is investigated. An advantage of MAHC over conventional reactors is an even temperature conductance in the reaction medium, as microwaves penetrate the whole reactor volume. This allows a better temperature control and a faster cooldown. Therefore, a succession of depolymerization, transformation and repolymerization reactions can be analyzed effectively. In this study, the analysis of the mass loss, ash content and composition, heating values and molar O/C and H/C ratios of the treated and untreated SCR willow wood showed that the mineral content of the MAHC coal was reduced and the heating value increased. The process water showed a decreasing pH and contained furfural and 5-methylfurfural. A process temperature of 170 degrees C showed the best combination of energy input and ash component reduction. The MAHC allows a better understanding of the hydrothermal carbonization process, while a large-scale industrial application is unlikely because of the high investment costs.